Effects of stocking density on growth and production of shing (Heteropneustes fossilis) in ponds - Rahman, Md Mamunur; Mondal, Debashis Kumar; Amin, Md Rurul; Billah, Masum (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
To assess the effects of stocking density on growth and production of shing (Heteropneustes fossilis)in ponds, an experiment was carried out for a period from 06 August to 22 December, 2015. Three stocking densities used were 80, 160 and 240 fish /decimal and designated as T1, T2 and T3, respectively. Each treatment has two replications. Shing having a mean body weight of 1.18g was used in T1, T2 and T3, respectively. A commercial feed fed at the rate of 50% of body weight up to first 15 days and then gradually it was readjusted to 35%, 25%, 15%, 5% and 2% respectively. The water quality parameters were monitored at 15 days interval and the ranges were: temperature 23.0 ºC to 30.25 ºC, pH 6.64 to 8.16, dissolved oxygen 4.91 to 6.99 mg/l and transparency 36.15 to 41.5 cm. Results showed that, the fish stocked at the rate of 80 fish/decimal in T1 get best individual weight gain (42.63g) followed by T2(38.52g) and T3 (34.82g), respectively. The SGR ranged between (1.77to1.81) %/day. There was significant variation (P<0.01) among the survival rate which ranged from 66.45% to 88.75%. The production was 3.02 kg, 4.96 kg and 5.55 kg/dec/134 days in T1, T2 and T3, respectively. But the highest production of 5.55kg/dec/134 days was obtained in T3 with stocking density of 240 fish/dec might be due to higher stocking density. Although the highest production was obtained in T3 but individual growth performance of shing (Heteropneustes fossilis) was highest in T1. The highest net profit was found (BDT 2591) in treatment T2 compared to treatments T1 (BDT 1800) and T3 (BDT 1479). The cost benefit ratios were 1.59, 1.48 and 1.10 % in T1, T2 and T3 respectively. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 380-385